Genome-Wide Association Mapping Analyses Applied to Polyamines - Barboza Barquero, Luis Orlando (2018)
Genome Wide Association Studies (GWAS) allow the use of natural variation to understand the genetics controlling specific traits. Efficient methods to conduct GWAS in plants have been reported. This chapter provides the main steps to conduct and analyse GWAS in Arabidopsis thaliana using polyamine levels as trait. This approach is suitable for the discovery of genes that modulate the levels of polyamines, and can be used in combination with different types of stress.